2019
DOI: 10.1111/apa.14780
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance and cognitive correlates in children cooled for neonatal encephalopathy without cerebral palsy at school age

Abstract: Aim: To investigate whether motor performance in school-age children without cerebral palsy (CP), cooled for neonatal encephalopathy, is associated with perinatal factors and 18month developmental scores and to explore relationships between school-age motor and cognitive performance.Methods: Motor and cognitive performance was assessed in 29 previously cooled children at six to eight years using the Movement Assessment Battery for Children-2 (MABC-2) and the Wechsler Intelligence Scale for Children (WISC-IV). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 28 publications
2
49
0
1
Order By: Relevance
“…TH reduces the chance of death and disability at 18 months ( Jacobs et al, 2013 ), reduces likelihood and severity of CP ( Jary et al, 2015 ) and increases the incidence of survival with an IQ > 85 ( Azzopardi et al, 2014 ). However, recent studies have shown that children aged 6–8 years, who underwent TH at birth for NE and did not develop CP, perform worse in motor and cognitive tests than controls ( Jary et al, 2019 , Lee-Kelland et al, 2020 ) and have attention difficulties, slower reaction times and reduced visuo-spatial processing abilities ( Tonks et al, 2019 ). These motor and cognitive deficits are not predicted by 18-month developmental scores ( Azzopardi et al, 2014 , Jary et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…TH reduces the chance of death and disability at 18 months ( Jacobs et al, 2013 ), reduces likelihood and severity of CP ( Jary et al, 2015 ) and increases the incidence of survival with an IQ > 85 ( Azzopardi et al, 2014 ). However, recent studies have shown that children aged 6–8 years, who underwent TH at birth for NE and did not develop CP, perform worse in motor and cognitive tests than controls ( Jary et al, 2019 , Lee-Kelland et al, 2020 ) and have attention difficulties, slower reaction times and reduced visuo-spatial processing abilities ( Tonks et al, 2019 ). These motor and cognitive deficits are not predicted by 18-month developmental scores ( Azzopardi et al, 2014 , Jary et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these regions were also shown to have reduced FA in the CoolMRI cases, indicating that the early structural alterations resulting from the brain injury cause lasting changes to white matter development. These results also provide evidence for an underlying white matter deficit which manifests as neuropsychological differences seen at school-age (Jary et al, 2019;Lee-Kelland et al, 2020;Tonks et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
“…As a demonstration, we then investigate tract-level differences in children treated with therapeutic hypothermia (TH) for neonatal encephalopathy (NE) at birth, compared with healthy controls, and compare results obtained using the age-specific atlas to those from the JHU atlas. The children who had TH, do not have CP and are in mainstream education still exhibit significantly reduced performance on cognitive tests (Jary et al, 2019;Lee-Kelland et al, 2020) and have slower reaction times and reduced visuo-spatial processing abilities (Tonks et al, 2019), compared to the typically developing controls.…”
Section: Introductionmentioning
confidence: 99%
“…These cognitive impairments are reflected by the significantly higher need for additional support at school in the case group . Case children with lower cognitive scores had lower motor performance scores on movement assessment battery for children—second edition . Furthermore, school‐aged children cooled for HIE and did not have CP have lower attention and visuospatial function compared to age, sex and social class matched controls …”
Section: Outcomes Of Children Without Cp Who Were Cooled For Hiementioning
confidence: 96%